IMPROVING THE STRENGTH OF DETAILS BY CHROMING THE SURFACES - Mukhtorov, Sherzodjon Sobirjon ugli; Rustamova, Mukhlisa Mukhtaraliyevna (Educational Research in Universal Sciences, 2022)
Development of an optimal option of electrolytic growth and plasma coating methods to improve the chromium strength of the surface of the parts and analysis of scientific and theoretical, practical confirmation of the solution.